The limits of stabilization infrastructure, public deficits, and growth in Latin America (Washington, D.C World Bank, 2003)
Latin America's macroeconomic crises of the 1980s and '90s forced a severe fiscal adjustment across the region. More often than not, fiscal stability was achieved at the cost of a drastic compression of public infrastructure spending, accompanied by the hope that the private sector would take the leading role in infrastructure provision.
Includes bibliographical references and index.
Keywords: Infrastructure (Economics)--Latin America